Lira i struna w poezji Zbigniewa Herberta - Wiśniewski, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
In Herbert’s poetry the words which are the names of musical instruments function both on the level of literary text stylistic composition - they are constituent elements of the metaphors and comparisons - and as signs of concrete or symbolic objects, which constitute one of the categories of motifs visible in the poems. The essay is an attempt to define the function performed by the motifs of the lyre and the lute, the first two instruments to appear in Zbigniew Herbert’s poetry. The group of poems in which the motifs of the lyre, the lute and the string - a frequent synexdoche of the two instruments - appear includes twelve poems: Do Apollina [To Apollo], O Troi [On Troy], Do Marka Aurelego [To Marcus Aurelius], Struna [The String], Las Ardeński [The Forest of Arden], Arijon [Arion, from the volume Struna Światła [The String of Light]), Niepoprawność [Incorrectness], Do Pięści [To the Fist], Prośba (A Request, from the volume Hermes, pies i gwiazda [Hermes, a Dog and a Star]), Apollo i Marsjasz [Apollo and Marsyas], Szuflada (The Drawer, from the volume Studium przedmiotu [A Study of an Object]), Wit Stwosz: Uśnięcie Najświętszej Marii Panny (Veit Stoss: Repose of the Virgin, from the volume Elegia na odejście [An Elegy on Passing Away]). In the symbolism of the poems by Zbigniew Herbert the motif of the lyre has ambivalent value. It symbolizes a type of art which does not suit twentieth century experiences or kind of poetry ruthlessly indifferent to evil and thus deserving ethical criticism on the one hand and represents art., which can provide man with a sense of the order of existence, on the other. It is because of the second function that is must be saved. In Herbert’s poems the lyre symbolizes classical poetry - its stylistic tone and function; it is also a symbol of music and harmony - presented as a desired state existing in the world. The string - if it is not a synexdoche of the lyre or the lute - becomes a symbol of new poetry, which results from twentieth century catastrophes, but does not totally reject classical tradition (though compared to it, it is only partial and incomplete). The way the two motifs function in Herbert’s poetry illustrates one of the author’s fundamental dilemmas. The question is: How can a poet who has rejected traditional classicism remain a twentieth century classical poet?